Modul Mentoring Adab Fase C Sekolah Dasar - Yuhdi, Yuhdi; Supraha, Wido; Mansur , Abas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of education is to form good character and character. However, the condition of civilization and character is deteriorating. Among his declines that Syed Muhammad Naquib Al-Attas called the loss of adab (Los of Adab) included speaking, behaving and dressing that was not in accordance with Islamic values. Cases of defiance to parents and teachers, bullying and violence committed by grade 5 and 6 elementary school students. The purpose of this study is to analyze how the concept of adab according to Syed Muhammad Naquib Al-Attas and Ali bin Nayef Ash-Syuhud, the development of adab at SDIT Ummul Quro Bogor and the mentoring module adab phase C elementary school. With qualitative methods, this research was carried out by literature review, direct observation and interviews according to the object of research. From the results of the analysis carried out, it is produced that adab is the right behavior born from personal discipline built on knowledge that emanates from wisdom. The adab development program at SDIT Ummul Quro Bogor is carried out with 8 habits habituation activities, scouts, morning meetings, extracurriculars, morning greetings, Islamic holiday celebrations, national holiday celebrations and infak habituation. The mentoring module for phase c of elementary school is adjusted to the achievements of mentoring activities / BPI where the material refers to the muashofat of a Muslim, including clean Aqedah, true worship, strong morals, physical strength, Intellect in thinking, Fighting Against Lust, Good at keeping time, organized in affairs, able to work alone or independently, benefiting others. The mentoring module is a solutive schedule in instilling good character in students.